The complete chronicles of Narnia - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 1998)
A collection of all seven volumes of the "Chronicles of Narnia," featuring original illustrations which have been colored by the artist.
The magician's nephew -- The lion, the witch and the wardrobe -- The horse and his boy -- Prince Caspian -- The voyage of the Dawn Treader -- The silver chair -- The last battle.
"Ages 8 and up"--Jacket.
Christian Library.
6.2.
6.2
5-8
Keywords: Fantasy; Fantastic fiction